A nanoelectromechanical systems actuator driven and controlled by Q-factor attenuation of ring resonator - Dong, Bin (2014)
In this Letter, an optical gradient force driven Nanoelectromechanical Systems (NEMS) actuator, which is controlled by the Q-factor attenuation of micro-ring resonator, is demonstrated. The actuator consists of a tunable actuation ring resonator, a sensing ring resonator, and a mechanical actuation arc. The actuation displacement can reach up to 14 nm with a measured resolution of 0.8 nm, when the Q-factor of the ring resonator is tuned from 15 × 103 to 6 × 103. The potential applications of the NEMS actuator include single molecule manipulation, nano-manipulation, and high sensitivity sensors.